Meningkatkan Customer Satisfaction Kartu Prabayar Simpati Telkomsel Dengan Service Quality, Brand Trust Dan Customer Experience - Nadhifah, Isyfa Fuhrotun; Ali, Ali; Setiawan, Wawan Edi (Universitas Islam Nahdlatul Ulama Jepara, 2023)
PT Telkomsel is one of the telecommunications companies that has the widest network compared to its competitors. Telkomsel has quality that is expected to be able to fulfill the desires of its customers. The Simpati card received the top ranking, reflecting the satisfaction and trust of telephone users towards Simpati products and services, so it can be interpreted that the Simpati card is the product most in demand by the public. Customer satisfaction is an important factor that must be achieved by the company in retaining its customers. This study aims to find out how Service Quality, Brand Trust and Customer Experience affect Customer Satisfaction of Telkomsel's Simpati prepaid card. The data analysis method used in this study is a quantitative analysis method. The object of this research is the Telkomsel Sympathy Prepaid Card. The method for determining the sample is purposive sampling, obtaining a sample of 100 people. The results of this study simultaneously that the variables service quality, brand trust and customer experience have an effect on customer satisfaction for Telkomsel prepaid cards, but partially service quality variables have no effect on customer satisfaction. Brand trust has an effect on customer satisfaction. and the customer experience variable influences customer satisfaction.